IMPLEMENTASI PROGRAM PEMBERDAYAAN ALTERNATIF MASYARAKAT PERKOTAAN PADA KAWASAN RENTAN NARKOBA DI KAMPUNG PERTANIAN JAKARTA TIMUR - Nopitasari, Dian; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
The implementation of these programs exist for handling social problems i.e. drug abuse conducted by the National Narcotics Agency through the efforts of prevention and eradication of Drug abuse and Dark Outlets (P4GN). This effort is conducted through a program of alternative Urban Community Empowerment which renders region Kampung farm, East Jakarta as targets or targets in its implementation. The purpose of this study was to describe the implementation of Alternative urban communities Empowerment Programme In the region Vulnerable to drugs in Agriculture in East Jakarta as well as to know the factor endowments and restricting factors of alternative urban communities Empowerment Programme In the region Vulnerable to drugs in Agriculture in East Jakarta. This type of research is a research dekriptif by using the pendekata method of the qualitative. The results showed that in practice there were indicators such as on the appropriateness of the policy in which to solve the problem have not yet seen a good run because the empowerment program takes a long time, precision implementation seen from the main actors and how the role of private parties and communities that want to get involved has gone well, the precision ofthe target associated with the intervention, objectives and community responses that have not been run well related to the environment, the precision of the internal and external environment the external environment which still lack in the mass mediato deliver news about the empowerment program alternatives, and the precision ofthe process related to the readiness of the implementing agencies and the communities where it is still not fully prepared to get involved. In the study also found an inhibitor factor is communication, resources, and disposition. Recommendations that can be given is associated with intensity about the socialization program, human resources and financial resources is related to the addition of officers in the field required and budget down in accordance with the schedule, and the disposition related to the willingness and commitment of the employees of improved returns.